A Comparative Study of Coverage Estimation and Quality of Service for DVB-H Urban Networks Using a Specialized RF Planning Software - Pantelis, Zafirios S.; Kotsopoulos, Stavros A. (Communications - Scientific letters of the University of Zilina, 2008)
The Digital Video Broadcasting – Handheld (DVB-H) standard is the ETSI standard for delivering broadcasting services of high data rates to handheld devices, under high mobility conditions. This paper will compare the different modulation techniques used by the DVB-H standard from the coverage point of view. The coverage estimation simulations have been made with a specialized RF planning tool using real Geographic Data for the metropolitan region of Athens. Thus, we will present a comparative study, of various planning factors like coverage percentage and location probability and compare them for the different modulation schemes used.